2017
DOI: 10.1016/j.meegid.2017.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Novel avian oropharyngeal trichomonads isolated from European turtle doves ( Streptopelia turtur ) and racing pigeons ( Columba livia ): genetic and morphometric characterisation of clonal cultures

Abstract: Extensive diversity has been described within the avian oropharyngeal trichomonad complex in recent years. In this study we developed clonal cultures from four isolates selected by their different ITS1/5.8S/ITS2 (ITS) genotype and their association with gross lesions of avian trichomonosis. Isolates were obtained from an adult racing pigeon and a nestling of Eurasian eagle owl with macroscopic lesions, and from a juvenile wood pigeon and an European turtle dove without clinical signs. Multi-locus sequence typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…From 1960 to 2020, the majority of studies concerning turtle doves investigated this game separately from other species that could exist in the same habitats, and this will miss a piece of precious information that would help in the conservation of this declining migrant bird [26]. In the best case, turtle doves were studied comparatively with conspecific competitors (Columbidae), such as laughing dove, collared dove, stock dove, and wood pigeon, mainly in geographical distribution [27][28][29][30][31][32], in feeding competition [29,33], in breeding biology [26,[34][35][36], and in parasite infestation [37,38]. On the contrary, this study has situated turtle doves among interspecific breeding species in wild nesting sites.…”
Section: Discussionmentioning
confidence: 99%
“…From 1960 to 2020, the majority of studies concerning turtle doves investigated this game separately from other species that could exist in the same habitats, and this will miss a piece of precious information that would help in the conservation of this declining migrant bird [26]. In the best case, turtle doves were studied comparatively with conspecific competitors (Columbidae), such as laughing dove, collared dove, stock dove, and wood pigeon, mainly in geographical distribution [27][28][29][30][31][32], in feeding competition [29,33], in breeding biology [26,[34][35][36], and in parasite infestation [37,38]. On the contrary, this study has situated turtle doves among interspecific breeding species in wild nesting sites.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported on the occurrence of T. tenax in the oral cavities of dogs and cats [ 3 , 29 ]. Recently, T. tenax was detected in the cloaca of birds [ 30 , 31 , 32 , 33 , 34 , 35 ]. With T. tenax being found in so many different hosts, it is important to determine whether T. tenax is a human parasite, which is the predominant current view, or if it is a parasite of animal origin with zoonotic potential.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Girard et al ( 2014b ) identified the new species T. stableri as the parasite involved in mortalities of band-tailed pigeons ( Patagioenas fasciata monilis , Vigors 1839). The existence of isolates with a high similarity to the human pathogens Trichomonas vaginalis (Donné 1836) and Trichomonas tenax (Muller 1773; Dobell 1939) and the canid pathogen Trichomonas canistomae were reported from Europe, Brazil and the USA (Gerhold et al 2008 ; Grabensteiner et al 2010 ; Ecco et al 2012 ; Martínez-Herrero et al 2014 , 2017 ; Quillfeldt et al 2018 ). The occurrence of hybrid lineages was also recently reported (Alrefaei et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%